INFLUENCE OF INTERPERSONAL RELATIONS ON THE SOCIAL AND PSYCHOLOGICAL ATMOSPHERE AT A STUDENT GROUP - Chaikovska, Oksana; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the results of theoretical and empirical analysis of the influence of interpersonal relationships on the social-psychological atmosphere at a student group. The authors understand the group social-psychological atmosphere as a specific social-psychological phenomenon, formed at a group under influence of a complex system of relations between the group members and with the surrounding social environment at work and communications. This atmosphere is manifested on emotional, behavioural, cognitive, moral and ideological planes and affects activities of individuals and the group. The influence of interpersonal relationships on the socio-psychological atmosphere at a student group is investigated in the empirical study. The performed empirical study shows that the prevailing type of communication in the two studied student groups is the authoritarian type of interpersonal relationships characterized by activity, aspiration to leadership; most of the active students want to be respected and love to give advices. The group of the fourth academic-year students has mainly averagely favourable psychological microclimate, which means that the psychological environment in this group is good; students feel comfortable and cosy in the group. The psychological microclimate at the group of the third academic-year students is unfavourable, which indicates that the students in this group feel mostly uncomfortable, constrained and not cosy. The correlations between the prevailing type of interpersonal relations in student groups and the social-psychological atmosphere in these groups have been empirically determined. The optimization of the social-psychological atmosphere in student groups can be facilitated by the following types of interpersonal relationships: friendliness and altruism. Subordination, suspicion and authoritarianism prevent formation of a favourable socio-psychological atmosphere. The revealed influence of interpersonal relationships on the social-psychological atmosphere of the student groups indicates the need for further determination and improvement of the methods influencing the group social-psychological atmosphere.